Bioguided fractionation from Solanum elaeagnifolium to evaluate toxicity on cellular lines and breast tumor explants - HERNÁNDEZ O., Leobardo; CARRANZA R., Pilar; COBOS P., Luis Enrique; LÓPEZ L., Lluvia Itzel; ASCASIO V., Juan Alberto; SILVA B., Sonia Yesenia (Vitae, 2017)
Background: Bioactive compounds were isolated from the fruit of S. elaeagnifolium, as it has a high potential for functional foods or pharmaceutical products development. Objectives: In this study bioguided fractionation a methanolic extract from S. elaeagnifolium fruit was carried out to evaluate cytotoxicity and antitumoral potential on breast tumor explants. Methods: A microdilution method with A. salina was used to isolate bioactive compounds; fractionation was performed by vacuum liquid chromatography, and the monitoring from fractions was done by thin layer chromatography. Moreover, toxicity from fractions isolated in Vero, HeLa, and MCF-7 cell lines was assessed by MTT assay, as well as in breast tumor explants by Alamar blue assay. To partially identify compounds was realized a qualitative phytochemical analysis as well as a spectroscopic characterization by Rp-HPLC-MS. Results: Were promising, as it was observed that FVLC7 showed an LC50= 44.8 ± 3.5 ppm on HeLa cell line, while Vero and MCF-7 cell lines showed an LC50=80.0 ± 8.5 and LC50 >1000 ppm respectively. Also, an antitumor effect was found in breast tumor explants obtained from a patient in remission. Qualitative phytochemical analysis showed that FVLC7 contains alkaloids, coumarins, and sesquiterpene lactones, whereas characterization by Rp-HPLC-MS detected quinic acid, chlorogenic acid, dicafeoilquinic acid as well as presence an alkaloid. Conclusion: Therefore, was confirmed that active compounds isolated from S. elaeagnifolium possess antineoplastic potential and that A. salina test facilitates its selection.